Gender bias in a patriarchal society; A media analysis on virginity and reproductive health - Sarwono, Billy K. (UI Scholars Hub, 2012)
Women and health are two very close issues as family health lies most often in the hands of women. Ironically, their awareness toward their own health is still low. Cultural constraints have made single, unmarried women or virgins feel reluctant to go to obgyn clinics, though there is an increasing prevalence of cervical cancer in Indonesia. Related to the role of the media to reduce the number of women with cervical cancer, a question rises. How do the media represent this conflict? The object of the study is a documentary film about several problems faced by women. The unit of analysis is the episode that contains issues related to the virtue of virginity, and data were collected through an analysis of the media text. The findings show that the media seem to have an awareness of the problems, but they have not fully adopted gender perspectives, and this leads to the strengthening of myths, taboos and traditional values surrounding virginity.